The Effectiveness of Integrated Farming Systems in Improving Household Food Security - Kamakaula, Yohanes; Baaka, Alnita (Westscience Press, 2025)
This study investigates the effectiveness of Integrated Farming Systems (IFS) in improving household food security in Indonesia using a quantitative approach. A total of 70 farming households were surveyed through structured questionnaires, with responses measured on a Likert scale (1–5). Data were analyzed using SPSS version 25, including descriptive statistics, reliability and validity testing, correlation, and regression analysis. The results show that IFS significantly and positively influence household food security, with the strongest effects observed on food availability and food accessibility, followed by food utilization and stability. Regression analysis confirmed that IFS explained 41.3% of the variance in household food security (β = 0.642, p < 0.001). These findings highlight that IFS not only increase food production and income but also contribute to dietary diversity and resilience against external shocks. The study concludes that integrated farming is an effective strategy to strengthen rural household food security and supports Indonesia’s broader goal of achieving sustainable food sovereignty.